Fiscal consolidations and bank balance sheets - Jacopo Cimadomo; Sebastian Hauptmeier; Tom Zimmermann (European Central Bank (ECB), 2013)
We empirically investigate the effects of fiscal policy on bank balance sheets, focusing on episodes of fiscal consolidation. To this aim, we employ a very large data set of individual banks' balance sheets, combined with a newly compiled data set on fiscal consolidations. We find that standard capital adequacy ratios such as the Tier-1 ratio tend to improve following episodes of fiscal consolidation. Our results suggest that this improvement results from a portfolio re-balancing from private to public debt securities which reduces the risk-weighted value of assets. In fact, if fiscal adjustment efforts are perceived as structural policy changes that improve the sustainability of public finances and, therefore, reduces credit risk, the banks' demand for government securities should increases relative to other assets.
Keywords: E62; G11; G21; H30; 330; bank balance sheets; banking stability; Fiscal consolidations; portfolio re-balancing